Systematic Review of IFRS, FDI, Institutional Quality, and Economic Growth - AL-Tuwaijari, Musatfa Rasim; Abdul Rahman, Mara Ridhuan Bin Che; Ahmad, Azlina; Abdul Rahim, Ruzita (Journal of Ecohumanism, 2024)
This article aims to review the work being done by scholars on the connection between FDI, as well as (IFRS), institutional quality, and economic growth literature by identifying the fundamental features of this connection and charting the research landscape that organizes the earlier work into a logical classification.The purpose of this literature review, which began in December 2023, was to provide a current and cutting-edge analysis of research on the connection of the relationship between (IFRS) and foreign direct investment (FDI). economic growth and institutional quality, as well as drawing attention to current research trends in this field. This methodology is different from other evaluations in that it focuses on assessing how IFRS adoption affects economic development by focusing on (FDI) as a mediating variable and how IFRS adoption affects the attractiveness of foreign direct investment.To find all articles about (IFRS), (FDI), the caliber of institutions, and economic growth, the survey searched four major databases: Scopus, Web of Science (WoS), Science Direct, and Emerald Insight. From 2014 to 2023, 3469 articles were found using the first search, which was conducted across 124 Scopus, 1481 Web of Science (WOS), 18 Science Direct, and 1846 Emerald Insight databases. These databases are sufficiently comprehensive to encompass the literature on (IFRS), FDI, and economic growth. 1887 articles were initially duplicated throughout the four databases. However, additional articles were eliminated in 1582 when titles and abstracts were scanned, leaving 223 studies in focus. Ultimately, 25 articles remain in the final included set after 198 articles are eliminated through full-text reading.The results of the literature review show that there is a lot of active and diverse research on the connection between (IFRS) adoption, Economic development, institutional integrity, and foreign direct investment; nevertheless, a more thorough examination of this link is required. For subsequent researchers to profit from this line of inquiry, this study believes that the survey has helped clarify the possibilities and gaps that are now accessible.